The Effect of Public Services on Community Satisfaction in the Capil Office, Muara Badak, Kutai Kartanegara Regency - Lukman, Rica Yulianti; Sultan, Nurul Fahmi; Ramadhani, Rezky (Jurnal Mirai Management, 2025)
This study aims to determine and analyze the effect of public services which consists of 3 dimensions of service quality as variables, namely responsiveness, reliability, and empathy to community satisfaction. This research approach uses a quantitative approach through primary data obtained by distributing questionnaires to people who have done management at the Capil Office of Muara Badak District with a sample of 100 people based on the minimum number of respondents for the Community Satisfaction Index. Sample data collection was done by accidental sampling technique. Based on the results of the analysis, it found from the results of research on factors that affect the satisfaction of the estuary rhino community, conclusions can be drawn from the three factors studied, namely Responsiveness, Reliability, and Empathy, all of these variables have a positive and significant effect on community satisfaction at the District Capil Office of Muara Badak, Kutai Kartanegara Regency. Keywords: Responsiveness, Reliability, Empathy, Community Satisfaction